Tinjauan Fikih Muamalah Tentang Penetapan Mu`Nah (Biaya Pemeliharaan Barang Gadai) pada Produk Arrum BPKB bagi UMKM di Pegadaian Syariah Kramat Raya Jakarta Pusat - Noor Uz’dmah Hayati; Syarif Hidayatullah; Hendra Kholid (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Based on the existence of a sharia pawnshop product called ARRUM BPKB which is specifically intended for UMKM (Usaha Mikro, Kecil dan menengah/Micro, Small and Medium Enterprises) who need additional capital. However, in the pawning process, the customer must pay the maintenance fee for the pawned goods or what is called mu'nah. Because of this additional cost in the process of maintaining the pawn item, there is an opinion that says that the additional maintenance costs contain riba. Therefore, the aims of this study is to find out how the determination of mu'nah (maintenance costs for pawn items) and the suitability of the determination of mu'nah based on Fiqh Muamalat. This research is Qualitative research with the type of case study. In this research, the analysis of various factors related to this problem was carried out. This research used an approach through observation to Pegadaian Syariah Kramat Raya, Central Jakarta. The primary sources in this study is the data collected by researchers from Sharia pawnshops, such as documents and interviews, while secondary sources in this study is relevant literature. The results of this study indicate, 1) the determination of mu'nah on ARRUM BPKB products in sharia pawnshops is by considering the risk amount of the guarantee itself. 2) Mu'nah determination on BPKB ARRUM products for UMKMs in Sharia Pawnshops is in accordance with Fikih Muamalah and Fatwa Number 92 / DSN-MUI / IV / 2014 regarding accompanied financing (Rahn Al-Tamwil Al-Mautsuq bi Al-Rahn) that mentions mu ' nah (maintenance or guarding services) for marhun, the amount of which must be determined at the time of the contract as referred to as ujrah in the ijârah contract.